Development of Spinning Wheel Learning Media on Plane Figures to Improve the Mathematics Learning Outcomes of Second-Grade Elementary School Students - Dhea Rahma Fajri (Global Journal Basic Education, 2026)
This study uses a Research and Development (R&D) approach with the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The analysis stage involves identifying learning needs, student characteristics, and problems encountered in mathematics learning, particularly on the topic of plane figures. The design stage focuses on planning the spinning wheel learning media, including the preparation of materials, questions, visual appearance, and media usage procedures. The development stage includes the creation of the media, product revision, and improvement based on development results. The implementation stage conceptually involves the use of the media in learning activities by engaging students actively through educational games. Finally, the evaluation stage includes theoretical assessment based on literature studies and previous research regarding the feasibility and effectiveness of the developed media. The results of the study indicate that the spinning wheel learning media on plane figures has the potential to improve students’ mathematics learning outcomes by creating a more active, interactive, and enjoyable learning atmosphere. The media helps students understand the concepts of plane figures more concretely through direct learning experiences. In addition, the use of the spinning wheel media can increase student engagement, learning motivation, and participation during the learning process. This study contributes to the development of innovative mathematics learning media that are appropriate to the characteristics of elementary school students and supports the implementation of meaningful learning.